Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Berpikir Kritis pada Mata Pelajaran PPKn di Kelas III MIN 3 Simalungun - Nadiyah Khairiyah; Auffah Yumni; Safran Safran (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to determine the feasibility of critical thinking-based Learner Worksheets (LKPD) in Civics subjects in Class III MIN 3 Simalungun. The background is that the Learner Worksheet used at MIN 3 Simalungun is an instant version of the publisher provided by the school not the result of the preparation carried out by the teacher himself. And printed with black ink on opaque paper. LKPDs found in schools are not yet based on critical thinking. Indicators of critical thinking have not been included in the LKPD, so it does not train students' critical thinking skills. This research is an R&D (Research and Development) study. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Researchers only limit it to the development stage. Researchers modify the development model as needed, because in terms of the formulation of the problem it is only limited to whether or not the LKPD will be developed. So, for this reason, researchers do not carry out the implementation and evaluation stages. Based on the results obtained after being validated by validators from 3 teams of experts, namely from material experts, a percentage of 94% was obtained which was declared very feasible. The assessment of the media expert showed a percentage of 88%, also declared very feasible. In addition, the assessment of linguists obtained a percentage of 86% and was declared very feasible. So it can be concluded